2016
DOI: 10.1007/s12663-016-0930-6
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of Fibula Free Flap in Reconstruction of Facial Defects: A Center Study

Abstract: Purpose To study a series of cases where vascularised fibula flap was used in various combinations of bone with muscle and skin along with its modifications for reconstruction of simple and composite defects of the facial region. Patients and MethodsThe investigators designed a retrospective study composed of patients with any pathology or defect who underwent reconstruction of maxilla or mandible with vascularised fibula free flap from 2009 to 2013. All patients were evaluated for age, gender, location and ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 21 publications
0
21
1
Order By: Relevance
“…The success rate of 79.8% found here is lower than other reports, probably because of the use of strict criteria to define failure and success: if a FFF was taken with a skin paddle and the skin paddle did not survive, this event was classified as a partial failure. If these salvaged flaps had been included in the success rate, a success rate of 87.6% would have been obtained, which is still slightly lower than other reports 3812. Four flap failures occurred more than 30 days after initial surgery.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The success rate of 79.8% found here is lower than other reports, probably because of the use of strict criteria to define failure and success: if a FFF was taken with a skin paddle and the skin paddle did not survive, this event was classified as a partial failure. If these salvaged flaps had been included in the success rate, a success rate of 87.6% would have been obtained, which is still slightly lower than other reports 3812. Four flap failures occurred more than 30 days after initial surgery.…”
Section: Discussionmentioning
confidence: 70%
“…It offers multiple advantages: the availability of ample bone length, the possibility of performing osteotomies for anatomical shaping, a versatile soft tissue unit with the option of multiple skin paddles, long vascular pedicles with an adequate diameter of the vessels, bicortical bone stock for dental implant placement, and the use of a two-team approach, reducing operating time 345. Overall success rates of free flap surgery are reported to be over 95%,6 and recent studies on free fibula flaps reported overall success rates of 90 and 93% 78. However, a subset of FFFs do fail, mostly because of arterial or venous thrombosis.…”
mentioning
confidence: 99%
“…The vascularized free fibula flap (VFFF), first introduced by Taylor et al 1 in 1975 and subsequently adapted to jaw reconstruction by Hidalgo 2 , is the most reliable and effective way to reconstruct facial composite bone and soft tissue defects [3][4][5][6] . In the last 40 years several other techniques including plates, local flap and other free flaps have been proposed without achieving the same morphological, aesthetic and functional outcome [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Tissue stretching can lead to local hypoesthesia and disaesthesia due to minor nerve impairment, whereas major abnormalities can be prevented by sparing the common peroneal nerve by preserving the first six centimeters of the fibula bone 12 . Thus, weakness, ankle instability, toe-deformity and difficulties in walking have been described as mixed muscular-nervous consequences of the flap removal 6,12-15 . Although the efficacy of the reconstruction has already been demonstrated in multiple publications 4,5,13 , few investigations described the donor site outcome after the harvest, generally using a qualitative approach based on clinical assessments 3,6,13,[16][17][18] . A quantitative evaluation after VFFF harvest through computerized gait analysis has been performed by few laboratories, often with non-concordant results due to different study protocols, as summarized in Table 1 3,10,12,14,[19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…The reconstruction of a mandibular defect with a vascularized free fibula flap is a well-established method [1]. A vascularized free fibula flap is longer, has long vascular pedicles that help in the mandibular reconstruction [2], and has been shown to be highly reliable and adaptable [3,4]. However, in addition to early complications such as a vascular crisis, long-term complications can occur between the grafted fibula bone and the host's native mandible [5][6][7], such as delayed healing or poor union, which compromise long-term stable occlusion and oral rehabilitation.…”
Section: Introductionmentioning
confidence: 99%